1992
DOI: 10.1007/bf01244816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subacute exposure to noise on the noradrenergic innervation of the cardiovascular system in young and aged rats: a morphofunctional study

Abstract: The effects of subacute noise stress on the noradrenergic pattern and receptor-mediated responses were examined in aorta and atria of young and aged rats. Noise exposure increased the density of noradrenergic fibres and responses to the beta-adrenergic agonist isoprenaline in the cardiac tissue of young animals. In aged rats, the stressing stimulus markedly increased the maximal response to the alpha-agonist on the aortic musculature; on the contrary, a reduced responsiveness to the beta-agonist was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Measurement of NA levels in specific areas of myocardial atrium and ventricle demonstrated the presence of higher amounts of this catecholamine in control tissue from the ventricle compared with that from the atrium (Table 1). Extending what was previously reported on the basis of histofluorescence qualitative measurements (Paparelli et al 1992), the amount of NA and its metabolites dihydroxymandelic acid and vanilmandelic acid in myocardial tissue after noise exposure indicated that loud noise increases NA levels and NA utilization. Increase in extracellular metabolites significantly exceeded increases in NA levels, leading to a significant rise in the turnover index (ratio between extracellular metabolites and NA).…”
Section: Dna Integritysupporting
confidence: 75%
See 2 more Smart Citations
“…Measurement of NA levels in specific areas of myocardial atrium and ventricle demonstrated the presence of higher amounts of this catecholamine in control tissue from the ventricle compared with that from the atrium (Table 1). Extending what was previously reported on the basis of histofluorescence qualitative measurements (Paparelli et al 1992), the amount of NA and its metabolites dihydroxymandelic acid and vanilmandelic acid in myocardial tissue after noise exposure indicated that loud noise increases NA levels and NA utilization. Increase in extracellular metabolites significantly exceeded increases in NA levels, leading to a significant rise in the turnover index (ratio between extracellular metabolites and NA).…”
Section: Dna Integritysupporting
confidence: 75%
“…In particular, here we found that noise exposure produces a significant increase of NA release as measured by myocardial levels of NA and metabolites. This latter finding lends substance to previous observations obtained in noise-exposed rats showing an increased fluorescence in the myocardial tissue as revealed by the histochemical technique of Falck-Hillarp (Paparelli et al 1992). These original findings did not address the functional relevance of an increased myocardial histofluorescence, leaving open the question of whether this was accompanied by increased NA release.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In particular, in the rat, heart noradrenergic innervation is reported to increase, following loud noise exposure (Breschi et al, 1994;Paparelli et al, 1992). At the same time, ultrastructural investigation shows that rat cardiomyocytes exhibit several subcellular changes (Paparelli et al, 1995;Soldani et al, 1997a).…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, experimental studies have demonstrated ultra structural modifications in rat cardiomyocytes mainly involving mitochondria. These subcellular alterations are related to an imbalance in calcium homeostasis, which is supposed to be sustained by increased catecholamine innervations (1).…”
Section: Introductionmentioning
confidence: 99%